2022
DOI: 10.1038/s41598-022-23955-7
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment of the health status and leisure activities of individuals on haemodialysis

Abstract: Self-assessment of health status is an important marker of social and health aspects. Haemodialysis is an option for renal replacement therapy that alters daily life and impacts social participation and the performance of tasks that give the subject a socially accepted role. In this scenario, leisure activities have the potential to generate well-being and are associated with several aspects of daily life, but few studies have analysed their relationship with the self-assessment of health status. This is a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
1
0
4
Order By: Relevance
“…(9,13) Somado a isso, as restrições alimentares do tratamento e sua duração pela vida inteira são fatores complementares que parecem dificultar a manutenção do tratamento nutricional por longo prazo. (14) Ao avaliar os fatores associados ao excesso de GPID nessa população, indivíduos com mais de 11 anos de escolaridade tiveram menor chance de GPID elevado, semelhante aos resultados de outro estudo que avaliou a adesão às restrições na ingestão de fluidos em 200 indivíduos em hemodiálise. (18)(19)(20)(21)(22) A relação entre educação e adesão ao tratamento é amplamente analisada.…”
Section: Discussionunclassified
“…(9,13) Somado a isso, as restrições alimentares do tratamento e sua duração pela vida inteira são fatores complementares que parecem dificultar a manutenção do tratamento nutricional por longo prazo. (14) Ao avaliar os fatores associados ao excesso de GPID nessa população, indivíduos com mais de 11 anos de escolaridade tiveram menor chance de GPID elevado, semelhante aos resultados de outro estudo que avaliou a adesão às restrições na ingestão de fluidos em 200 indivíduos em hemodiálise. (18)(19)(20)(21)(22) A relação entre educação e adesão ao tratamento é amplamente analisada.…”
Section: Discussionunclassified
“…(9,13) Somado a isso, as restrições alimentares do tratamento e sua duração pela vida inteira são fatores complementares que parecem dificultar a manutenção do tratamento nutricional por longo prazo. (14) Ao avaliar os fatores associados ao excesso de GPID nessa população, indivíduos com mais de 11 anos de escolaridade tiveram menor chance de GPID elevado, semelhante aos resultados de outro estudo que avaliou a adesão às restrições na ingestão de fluidos em 200 indivíduos em hemodiálise. (18)(19)(20)(21)(22) A relação entre educação e adesão ao tratamento é amplamente analisada.…”
Section: Discussionunclassified
“…Estudo de censo epidemiológico transversal com coleta de dados de todos os centros de hemodiálise de uma Região Metropolitana do Sudeste do Brasil em 2019, de acordo com estudos publicados anteriormente. (6,14) O estudo incluiu indivíduos do sexo masculino e feminino, maiores de 18 anos, em hemodiálise, que atenderam aos seguintes critérios de inclusão: diagnóstico confirmado de doença renal crônica e em terapia hemodialítica há pelo menos três meses. Os seguintes indivíduos foram excluídos Resumen Objetivo: Evaluar los factores asociados al aumento de peso interdialítico en usuarios de servicios de hemodiálisis en una región metropolitana de Brasil.…”
Section: Métodosunclassified
See 1 more Smart Citation
“…Moreover, health self-assessment, a subjective measure of individuals' health perception, plays a crucial role in understanding residents' health and well-being. In this method, the simple Likert scale scoring method allows individuals to independently rate their health based on subjective feelings, and thanks to its simplicity, it has been widely adopted by scholars [ 25 , 26 ]. Leveraging available data, this study employs respondent-reported health self-assessment as the dependent variable.…”
Section: Introductionmentioning
confidence: 99%